Generative artificial intelligence tools to augment teaching scientific research in postgraduate studies - Segooa, M. A.; Modiba , F. S.; Motjolopane, I. (South African Journal of Higher Education, 2025)
Scientific research is the cornerstone of postgraduate studies. However, various challenges hinder the progression and success of postgraduate students, which also affects throughput, students experiencing challenges in formulating their proposals due to limited knowledge of problematising their research.Too much time goes into the proposal phase, either prolonging the study period or abandoning the research project. Modern generative artificial intelligence (AI) tools can now support the research process. This article aims to present a research tool supporting facilitators in the African context to integrate various AI tools in postgraduate research teaching and learning. A systematic literature review was used to analyse research articles and grey literature; thus, identifying the review steps and tools which developed the ResearchBuddie artefact, supporting the research activities. Generative AI tools such as ChatGPT, Elicit, and Research Rabbit assist research activities. However, these tools must be made more cohesive and easier to use for all students. Therefore, increasing awareness and accessibility must be facilitated such that these tools can be leveraged to support the research process. A tool, such as the ResearchBuddie artefact, may accelerate the writing process and enhance the quality of the proposal. The ResearchBuddie may also assist postgraduate students in other research processes as they conduct their studies, primarily the literature review section. Additionally, the supervisors may use the ResearchBuddie artefact to augment their supervision; more so, this could be a valuable tool for educators who teach postgraduate research programmes.